Influence of Influencer Marketing, Fear of Missing Out (FOMO), and Trust on Crypto Asset Purchase Decisions among Generation Z in Discord Miracle Class - Kurniawan, Ezra Tri; Zuchroh, Imama (PT. Riset Press International, 2025)
This study aimed to determine the effect of Influencer Marketing, Fear of Missing Out (FOMO), and Trust on crypto asset purchase decisions among Generation Z participants in the Discord Miracle Class community. The research employed quantitative methodology and applied Partial Least Squares (PLS) analysis using SmartPLS software version 4.1.0.9. Data were collected from 94 respondents who are active members of the Discord Miracle Class community through online questionnaires. The results demonstrated that Influencer Marketing had a positive and significant effect on crypto asset purchase decisions among Generation Z (path coefficient = 0.421, p < 0.05). FOMO also exhibited a positive and significant effect on crypto asset purchase decisions (path coefficient = 0.312, p < 0.05). Similarly, Trust showed a positive and significant influence on crypto asset purchase decisions in the same demographic (path coefficient = 0.389, p < 0.05). The combined effect of these three variables explained 72% of the variance in purchase decisions (R² = 0.720). This study contributes to the development of literature in digital consumer behavior and financial technology adoption, particularly in the context of crypto asset investment among Generation Z. The findings provide valuable insights for marketers, financial institutions, and policymakers in understanding the psychological and social factors that drive cryptocurrency investment decisions among young digital natives.